Islam, Ekskomunikasi, Dan Persoalan Penyesatan: Kajian Teo-Sosio-Analisis Atas Vonis Bid‘Ah, Riddah, Dan Kufr - Yusuf Hanafi (Universitas Islam Negeri Mataram, 2007)
The Muslims’ responses toward and understanding about the texts of Qur’an and hadîts—usually named as living Qur’an/tafsîr and living hadîts/sunnah—are of the objects of Islamic studies. Such responses include the Muslims’ reception and their interpretations toward certain texts and exegete found in the Muslims’ daily life, such as traditionalizing of recitation of certain chapters and verses of Qur’an in some social religious ceremonies and celebration. The social reception of the interpretations take form of either small or large scale of institutionalization. The Muslims’ responses toward and understanding about the texts of Qur’an and hadîts and their receptions do not cause any problems until the emergence of authorities in the Muslims’ communities that accuse them as heresy (bid‘ah), apostasy (riddah), and infidelity (kufr). This becomes the starting point of perverting and excommunication phenomena in Islam. This article is aimed at elaborating that problem and analyzing the phenomena through Theo-social-analysis.